EEG Identity Authentication in Multi-Domain Features: A Multi-Scale 3D-CNN Approach - Zhang, Rongkai; Zeng, Ying; Tong, Li; Shu, Jun; Lu, Runnan; Li, Zhongrui; Yang, Kai; Yan, Bin (Frontiers in Neurorobotics, 2022)
EEG authentication has become a research hotspot in the field of information security due to its advantages of living, internal and anti-stress. However, the performance of identity authentication system is limited by the inherent attributes of EEG, such as low SNR, low stability and strong randomness. Researchers generally believe that the in-depth fusion of features can improve the performance of identity authentication, and have explored among various feature domains. This experiment invited 70 subjects to participate in the EEG identity authentication task, and the experimental materials were visual stimuli of the self and non-self names. This paper proposes an innovative EEG authentication framework, including efficient three-dimensional representation of EEG signals, multi-scale convolution structure, and the combination of multiple authentication strategies. In this work, individual EEG signals are converted into spatial-temporal-frequency domain three-dimensional forms to provide multi-angle mixed feature representation. Then, the individual identity features are extracted by the various convolution kernel of multi-scale vision, and the strategy of combining multiple convolution kernels is explored. The results show that the small-size and long-shape convolution kernel is suitable for ERP tasks, which can obtain better convergence and accuracy. The experimental results show that the classification performance of the proposed framework is excellent, and the multi-scale convolution method is effective to extract high-quality identity characteristics across feature domains. The results show that the branches number matches the EEG components number can obtain the excellent cost performance. In addition, this paper explores the network training performance for multi-scale module combination strategy, and provides reference for deep network construction strategy of EEG signal processing.